The role of endoplasmic reticulum‐related BiP/GRP78 in interferon gamma‐induced persistent Chlamydia pneumoniae infection. (24th February 2015) - Shima, Kensuke; Klinger, Matthias; Schütze, Stefan; Kaufhold, Inga; Solbach, Werner; Reiling, Norbert; Rupp, Jan
Summary Direct interaction of Chlamydiae with the endoplasmic reticulum (ER) is essential in intracellular productive infection. However, little is known about the interplay between Chlamydiae and the ER under cellular stress conditions that are observed in interferon gamma (IFN‐γ) induced chlamydial persistent infection. ER stress responses are centrally regulated by the unfolded protein response (UPR) under the control of the ER chaperone BiP/GRP78 to maintain cellular homeostasis. In this study, we could show that the ER directly contacted with productive and IFN‐γ‐induced persistent inclusions of Chlamydia pneumoniae (Cpn). BiP/GRP78 induction was observed in the early phase but not in the late phase of IFN‐γ‐induced persistent infection. Enhanced BiP/GRP78 expression in the early phase of IFN‐γ‐induced persistent Cpn infection was accompanied by phosphorylation of the eukaryotic initiation factor‐2α (eIF2α) and down‐regulation of the vesicle‐associated membrane protein‐associated protein B. Loss of BiP/GRP78 function resulted in enhanced phosphorylation of eIF2α and increased host cell apoptosis. In contrast, enhanced BiP/GRP78 expression in IFN‐γ‐induced persistent Cpn infection attenuated phosphorylation of eIF2α upon an exogenous ER stress inducer. In conclusion, ER‐related BiP/GRP78 plays a key role to restore cells from stress conditions that are observed in the early phase of IFN‐γ‐induced persistent infection.